2022
DOI: 10.1111/his.14718
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkinoid histiocytosis: an atypical nodal CD30 and S100‐positive histiocytosis with eosinophilia

Abstract: Hodgkinoid histiocytosis: an atypical nodal CD30 and S100-positive histiocytosis with eosinophiliaHistiocytes and dendritic cells may display cytological atypia and an aberrant immunophenotype even in reactive processes. Herein, we describe two cases of "Hodgkinoid histiocytosis" that show distinctive clinicopathological features, mimicking morphologically classic Hodgkin lymphoma (CHL), but suggesting reactive histiocytic/dendritic cell proliferation in lymph nodes. Both the patients presented with peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Therefore, patients with histiocytosis discovered during the evaluation for eosinophilia should be offered bone marrow examination and testing for recurrently mutated myeloid genes. Hodgkinoid histiocytosis—a very rare entity—presents with eosinophilia and may mimic lymphoma ( 107 ).…”
Section: Review Of the Eosinophil Granulocyte In Health And Diseasementioning
confidence: 99%
“…Therefore, patients with histiocytosis discovered during the evaluation for eosinophilia should be offered bone marrow examination and testing for recurrently mutated myeloid genes. Hodgkinoid histiocytosis—a very rare entity—presents with eosinophilia and may mimic lymphoma ( 107 ).…”
Section: Review Of the Eosinophil Granulocyte In Health And Diseasementioning
confidence: 99%
“…Tsuyama et al more recently reported unique cases of Hodgkinoid histiocytosis with CHL-like morphologic features and CD30 and PD-L1 expression in Hodgkinoid histiocytes. 44 This diagnostic term, “Hodgkinoid”, was created by Tsuyama et al in order to avoid confusion with CHL, which is now defined as GC-derived B-cell neoplasm in the 2022 WHO classification. An international consensus should be achieved for these issues.…”
Section: Introductionmentioning
confidence: 99%